PROFIL PEMECAHAN MASALAH INTEGRAL DITINJAU DARI GAYA BELAJAR SISWA KELAS XII SMA KARYA BAKTI MAMBORO - Kelengi, Fadlun Wahyuni; Pathuddin, Pathuddin; Murdiana, I Nyoman (Jurnal Elektronik Pendidikan Matematika Tadulako, 2022)
This study aims to obtain a description of the integral problem solving profile in terms of the learning style of class XII high school students. The results of this study are: 1) An integral problem solving profile in terms of visual learning styles, namely: a) reading and thinking, the subject reads the question once without making a sound, then identifies the information on the question, b) explores and plans, the subject plans using the formula s(t)= c) choose a strategy, the subject explains while writing it on the scratch paper how to use the formula, d) finds the answer, the subject explains in detail and occasionally calculates the multiplication results on the scratch paper, e) reviewing, the subject rechecked the answer using the substitution method. 2) Integral problem solving profile in terms of auditory learning style, namely: a) reading and thinking, the subject reads the question repeatedly in a low voice, then identifies information on the question, b) explores and plans, the subject plans using the formula s(t)=c) choose a strategy, the subject explains how to use the formula, but does not write it down in detail, d) finds the answer, the subject explains the answer while occasionally looking at the researcher, e) revisits, the subject rechecks the steps solution step. 3) Integral problem solving profile in terms of kinesthetic learning style: a) reading and thinking, the subject reading the questions repeatedly and using a pen as a pointer, b) exploring and planning, the planning subject will use the formula s(t)= c)choosing a strategy, the subject hesitates in explaining the answer, because he made an error in the integral process, d) finds the answer, the subject explains while pointing at the answer sheet with a pen, e) reviews again, the subject does not re-check the answer.Keywords: Profile, problem solving Krulik and Rudnick, learning styles